DLC1 Is a Prognosis-Related Biomarker Correlated With Tumor Microenvironment Remodeling in Endometrial Carcinoma - Wu, Yalan; Zheng, Li-e; Chen, Shumin; Lv, Chengyu; Huang, Yuxiu (Frontiers in Oncology, 2022)
Background. Deleted in liver cancer 1 (DLC1) was supposed to be confirmed as a metastasis suppressor gene in endometrial carcinoma (EC), however, its functional mechanisms remain not exactly clear. Methods. The Cancer Genome Atlas (TCGA) database was used only for evaluating the expression of DLC1 in pan-cancer, after which TIMER was used to assess the association between DLC1 and tumor immune infiltration. Finally, we applied real-time quantitative PCR to determine the expression of DLC1 in endometrial carcinoma and adjacent normal tissue samples for further verification. Results. We identified DLC1 expression was significantly associated with the results in multiple types of cancer particularly evident in endometrial carcinoma. DLC1 expression was further analytical that it was negatively connected with the clinical characteristics (clinical-stage, Histologic grade) and positively related with the survival of uterine corpus endometrial carcinoma (UCEC) patients. Gene Set Enrichment Analysis (GSEA) displayed that the low-expression DLC1 group was enriched in metabolic pathways. Concomitantly, the high expression of the DLC1 group was primarily enriched in tumor immune-related activities. The proportion of tics that were analyzed by CIBERSORT showed T cells CD4 memory resting and mast cells resting were positively correlated with DLC1 expression, indicating that DLC1 is a determines factor that mediates the recruitment of immune cells to endometrial carcinoma tumors. It potentially played a key role in mediating immune cell infiltration. Successively, target gene validation confirmed that DLC1 expression was downregulated in the tumor samples. Conclusions. Therefore, DLC1 levels might be useful in predicting the prognosis of UCEC patients and especially governing the status of TME transition from immune-dominant to metabolic activity, which put a different light on the immune therapeutics of UCEC.